Hubungan perancangan sumber manusia dengan kepuasan kerja pekerja: Satu kajian empirikal - Tang, Swee Mei; Adnan, Zurina; Wan Daud, Wan Din (2017)
This study aims to explore the relationship of human resource planning practices (HRP) and employee job satisfaction among manufacturing companies in Malaysia.A total of 102 respondent companies involved in this study. The results showed that HRP had gained more attention and emphasis by the respondents. The correlation analysis showed that there was a correlation between HRP and organizational employee job satisfaction.In addition, simple linear regression model was developed to analyze the relationship between human resource planning and employee job satisfaction.Regression analysis results showed that HRP practices contributed 14.8% of the variance in employee job satisfaction.These findings indicate that HRP practices can contribute to job satisfaction of employees in the organization.